PERSEPSI PENGARUH FRAUD TRIANGLE TERHADAP PENCURIAN KAS - Mery Marliani (Business Accounting Review, 2015)
The purpose of this study was to collect evidence of three fraud factors which are influence cash theft. They were pressure, opportunity, and razionalitation that depent on employee’s perception.Data were obtained by distributing questionnaire and by using multiple regression analysis. The results from this study showed that there were positive significant affect of pressure, opprtunity, and razionalitation in cash theft.